Understanding the implications of artificial intelligence on field service operations: a case study of BT. Issue 16 (10th December 2022) - Wang, Yingli; Skeete, Jean-Paul; Owusu, Gilbert
Abstract: Driven by insufficient empirical research and understanding about AI deployment in operations management, we set out to explore the implications of AI on field service operations. Via an in-depth case study of four AI initiatives across a time span of 20 years at BT telecommunications, we explored the answers to the following two research questions (RQs): RQ1: How has the deployment of artificial agents affected the operational efficiency of the organisation? And RQ2: What are the critical success factors (CSFs) of AI deployment? Our study found that having a standard TRL protocol, a people-centric approach, as well as establishing a portfolio of AI initiatives are instrumental to BT's success. We also identified a range of other CSFs that were essential to the successful deployment of AI in BT's field service operations. This paper therefore contributes to the timely and emerging sociotechnical debates around the real-world implications of AI deployment within organisations.